Residential Care Institutions: Disciplinary Society or Social Work Institutes? - Rimšaitė, Eglė (Sociologija. Mintis ir veiksmas, 2006)
One of the most established forms of care for people with mental disabilities and mental illnesses in the former Soviet Union and in Central and Eastern Europe was treatment in large institutions – psycho neurological care homes. From one side, these institutions are integral part of social care systems and they pursue goals of social work: integration, inclusion, clients’ needs satisfaction. From the other side, various scientists portray institutions of this type as totalitarian institutions (Tobis, 2000) or disciplinary society institutions (Foucault, 1998),criticize them for violation of human rights and humiliation of human dignity.From the outlook of two confronting perspectives, the following article discusses the main mission of these institutions: promoting integration to society by supplying social services or aggravating the social exclusion by limiting residents’ rights, possibilities and privacy.
Keywords: care homes; institution; social work; disciplinary society